Information Technology Competencies, Organizational Agility, and Firm Performance: Enabling and Facilitating Roles - Chakravarty, Anindita; Grewal, Rajdeep; Sambamurthy, V. (Information Systems Research, 2013)
The hypercompetitive aspects of modern business environments have drawn organizational attention toward agility as a strategic capability. Information technologies are expected to be an important competency in the development of organizational agility. This research proposes two distinct roles to understand how information technology competencies shape organizational agility and firm performance. In their enabling role, IT competencies are expected to directly enhance entrepreneurial and adaptive organizational agility. In their facilitating role, IT competencies should enhance firm performance by helping the implementation of requisite entrepreneurial and adaptive actions. Furthermore, we argue that the effects of the dual roles of IT competencies are moderated by multiple contingencies arising from environmental dynamism and other sources. We test our model and hypotheses through a latent class regression analysis on data from a sample of 109 business-to-business electronic marketplaces. The results provide support for the enabling and facilitating roles of IT competencies. Moreover, we find that these dual effects vary according to environmental dynamism. The results suggest that managers should account for (multiple) contingencies (observed and unobserved) while assessing the effects of IT competencies on organizational agility and firm performance.